Decree on the Payment of Restitution to Deceased Perpetrators of Corruption - Muchsin, Mohammad; Suparji; Rifa’i, Anis (Jurnal Cakrawala Hukum, 2024)
This research is based on a case related to the recovery of financial losses suffered by the state due to a criminal act of corruption in the legal regulations. However, some problems lead to the implementation of the law being hampered when the defendant in the trial is proven to have committed a criminal act of corruption and is proven to have received the proceeds of corruption. This becomes a problem of what status and to whom the restitution is charged if the perpetrator of a corruption crime, who is strongly indicated to have received the proceeds of corruption, has died before being convicted. The research method in this journal is the normative legal method. The result is that this legal vacuum causes sharp differences in judges’ views and is still not by the provisions of the law governing the issue. The prosecutor does not have a clear legal umbrella to file a civil suit against the heirs of the offender who has died. In the future, problems will arise when similar cases occur, so there is no guarantee of legal certainty. The principle of legal certainty must be prioritized as a state of law that prioritizes the basis of legislation, decency, and justice in every policy of state administrations.